Preparing children for success in school and life : 20 ways to enhance your child's brain power - Tate, Marcia L. (Thousand Oaks, Calif. : Corwin, 2011)
'Marcia Tate's Preparing Children for Success in School and Life: 20 Ways to Enhance Your Child's Brain Power is an authoritative and practical guide for parents who are interested in creating a brain-compatible home environment conducive to the optimal growth and development of their children. In this collection of recommended best practices, Tate draws on what we know about how our brains behave and learn, the latest research in human growth and development, and her 30 years of being a mother to three to explain how parents can design a brain-compatible environment, put a plan into place to help children develop character and responsible behavior, and use key strategies that grow children's brain cells while working with them at home. Similar in format to Tate's other books, Preparing Children for Success in School and Life: 20 Ways to Enhance Your Child's Brain Power will define recommended practices, share research from the fields of psychology and education to demonstrate why the practices should be used, and provide numerous examples on the use of the practice in the home environment'--Provided by publisher.
Machine generated contents note: About the Author Foreword Acknowledgments Publisher's Acknowledgments Introduction Section I: Preparing Children for Success in Life 1. Develop a Relationship with Your Child 2. Hug, Rock, and Love Your Child 3. Surround Your Child with a Calming Environment 4. Give Your Child a Brain-Healthy Start 5. Talk to and with Your Child 6. Read to and with Your Child 7. Provide Opportunities for Creative Play 8. Teach Your Child Rules, Rituals, and Responsibility 9. Accentuate the Positive 10. Deemphasize the Negative 11. Identify Chronic Behavior and Mood Disorders 12. Expect the Best and Visualize Success Section II: Preparing Children for Success in School 13. Laugh and Have Fun, It's Good for You and Your Child 14. Stengthen Your Child's Auditory Mode of Learning 15. Strengthen Your Child's Visual Mode of Learning 16. Strengthen Yuor Child's Kinesthetic Mode of Learning 17. Strengthen Your Child's Tactile Mode of Learning 18. Make Memories with Music 19. Connect Content with Your Child's Life 20. Partner with Your Child's Teachers Afterword Parental Action Plan/Contract Bibliography Index .
Includes bibliographical references and index.
Keywords: Child development; Children -- Intelligence levels; Cognition in children; Parenting; Education -- Parent participation